Role of magnetic resonance imaging in assessment of relationship between intercondylar notch parameters and anterior cruciate ligament injuries - Nadine Hamdy Abdel Reheem; Ali Abdel Karim Farahat; Ihab Badawi; Rim Bastawi (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background The anterior cruciate ligament (ACL) is regarded as the primary stabilizer of the knee joint, and it is commonly injured. Anatomical features are thought to be the root causes of ACL tears. It is closely associated with the appearance and dimensions of the intercondylar notch. The aim of this work was to assess the relationship of parameters and morphological appearance of intercondylar notch in cases with ACL injuries using magnetic resonance imaging. Results A positive correlation was found between A-shaped intercondylar notch and increased incidence of ACL injury. The mean intercondylar notch width (NW) and intercondylar notch width index (NWI) were found to be smaller in ACL-injured group. Intercondylar notch angle was found to be wider in patient’s group. By comparing different intercondylar notch parameters in both genders, only notch width was found to be significantly narrower. No significant correlation was noticed between the type of tear and the intercondylar notch parameters. Both NW and NWI were found to be significantly narrower in patients with twisting injury during performing daily routine activities as compared to the other mechanisms of injury. Conclusions Our study showed that intercondylar notch parameters including notch type may contribute in increasing risk of anterior cruciate ligament injuries with stenotic intercondylar notch enhancing the likelihood of an ACL injury.